Nowoczesny Museion Jerzego Ludwińskiego - de Rosset, Tomasz F. (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
This paper is devoted to never fulfilled museum projects by Jerzy Ludwiński, one of the most outstanding Polish art critics of the 20th century. Although his idea of “Museum of Contemporary Art”(1966) and a bit later “Centre of Artistic Research”(1971) appeared on the other side of the Iron Curtain, they were at that time an innovative equivalent to discussions conducted in the west countries on the role of a museum as a traditional institution towards contemporary artistic activity. The traditional character and museum narrative were becoming more and more inadequate for changing art going beyond old barriers of different artistic genres and putting more and more pressure on a creative process at the expense of its result. Instead of a museum strictly subjected to historically arranged and exhibited collections, Ludwiński suggested a fully open attitude to the latest artistic tendencies, action and development of relations between an artist and his audience. The author compares these ideas to the one of the ancient Museion in Alexandria, the etymological ancestor of a modern museum. Such institution, which would change itself from the one of a static collection of works of art presented for individual and passive contemplation of an audience into a place where art is created, some kind of a laboratory or atelier, he interprets as an “Alexandria model of a museum”. He is against the more traditional one (called “Luxembourg” after Musee du Luxembourg in Paris established in 1819, the first museum of modern art), where works of contemporary art are shown only provisionally or are just kept in storerooms waiting for the prestige of passing time to prove their value.